Review of “Cataract: toxic, congenital, secondary”, a monograph by N.F. Bobrova and Z. M. Skripnichenko (Ukrainian Journal of Ophthalmology, 2026)
The monograph by Prof. Nadezhda F. Bobrova and Prof. Zinaida M. Skripnichenko is devoted to a current issue of ophthalmology, which is surgical treatment for various cataracts including toxic, congenital, secondary ones. The paper consists of seven parts on etiology, clinic, classification, and surgical technique features for each type of cataract.